Socio- economic impact of Krishi Mahotsav on Beneficiary Farmers of Gujarat - Pandya, S.P.; Prajapati, M. R.; Thakar, K. P. (Indian Journal of Extension Education, 2015)
Transfer of scientific technologies from research station to farmers' fields plays the vital role for rural development and  rural upliftment. The government of Gujarat organizes Krishi Mahotsav every year before monsoon. It is a unique approach of transfer of technology in the whole rural area. There are 18000 villages in Gujarat and Krishi Rath equipped  with scientific technology information through posters, panels, TV moves in every village. The scientists of agricultural  universities are appointed to deliver latest technical know-how. It was started in 2005 and designed for the benefits of  farming community for one month duration. Eight Krishi Mahotsav have been completed till this study. The present study  was conceived with a general objective of assessing the socio economic impact of Krishi Mahotsav on beneficiary farmers  as a result of participating in Krishi Mahotsav. Four districts of Gujarat state Banaskantha, Mahesana, Sabarkantha and  Kachchh were randomly selected for this study. The results revealed that majority of beneficiary farmers were found in  medium category of socio-economic impact as a result of participation in Krishi Mahotsav. About aspect-wise socioeconomic impact, majority of beneficiary farmers (43.33 %) have increased their cultivation land as a result of  participating in Krishi Mahotsav and 95 per cent beneficial farmer have increased their annual income per hectare.  According to the, opinion of the beneficiary farmers 57.08 per cent of them had increased their saving and investment,  67.92 per cent of them increased their social status and 72.50 per cent of the beneficiary farmers increased their social  relationship through participation in Krishi Mahotsav.
Keywords: Krishi Mahotsav; Transfer of technology; Socio economic impact